2019
DOI: 10.4250/jcvi.2019.27.e16
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Isolated Focal Right Ventricular Dyskinetic Segments: Toward a Better Understanding of This Cohort

Abstract: BACKGROUND The 2010 revised Task Force criteria for the diagnosis of arrhythmogenic right ventricular cardiomyopathy (ARVC) provided guidance for the classification of patients as definitive, borderline or possible ARVC. However, many patients with clinical suspicion for ARVC have isolated RV dyskinetic segments only and partly meet cardiac magnetic resonance (CMR) imaging criteria. This subgroup of patients and the implication of this imaging finding remain not well defined. METHOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In addition, it remains difficult to differentiate normal variations in RV wall motion near the moderator band insertion and pathological RV wall motion abnormalities by CMR 7). In this issue of the Journal of Cardiovascular Imaging , Mansour MJ et al10) assessed the CMR findings of 65 patients with clinically suspected ARVC (definite or borderline ARVC in 5 [7.7%] patients, isolated focal dyskinetic RV segments in 27 [41.5%] patients, and no RV dyskinetic segments in 33 [50.8%] patients). They found that 27 patients with isolated RV dyskinetic segments had slightly lower RVEF (55 ± 7% vs. 57 ± 5%), larger RV end-diastolic volume indices (82 ± 12 ml/m 2 vs. 72 ± 12 ml/m 2 , p = 0.0127), and a trend for higher odds of dilated right ventricle (odds ratio 3.0 [0.81-11], p = 0.09) compared to 33 patients with no ARVC.…”
mentioning
confidence: 99%
“…In addition, it remains difficult to differentiate normal variations in RV wall motion near the moderator band insertion and pathological RV wall motion abnormalities by CMR 7). In this issue of the Journal of Cardiovascular Imaging , Mansour MJ et al10) assessed the CMR findings of 65 patients with clinically suspected ARVC (definite or borderline ARVC in 5 [7.7%] patients, isolated focal dyskinetic RV segments in 27 [41.5%] patients, and no RV dyskinetic segments in 33 [50.8%] patients). They found that 27 patients with isolated RV dyskinetic segments had slightly lower RVEF (55 ± 7% vs. 57 ± 5%), larger RV end-diastolic volume indices (82 ± 12 ml/m 2 vs. 72 ± 12 ml/m 2 , p = 0.0127), and a trend for higher odds of dilated right ventricle (odds ratio 3.0 [0.81-11], p = 0.09) compared to 33 patients with no ARVC.…”
mentioning
confidence: 99%